Diseño, implementación y evaluación de un sistema de riego por microaspersión en café (Coffea Arábica l.) en la ESPAM MFL. - Mendoza Balderrama, Julio César (2015)
This research work was conducted in 2013, in teaching, research, production and linking the university campus ESPAM "MFL" area it was developed with the aim of implementing a micro sprinkler irrigation system in a total area of 7035m2 to ensure the volume of water required for the cultivation of coffee (Coffea arabica L) .For the implementation of the agronomic and hydraulic system design that allowed the calculation of crop water requirements and system components was performed. To set the frequency and dosage of irrigation needed by the coffee plant, physical and chemical soil studies were performed, according to the agronomic irrigation design a sheet of 725 mm according to microaspersor elect is necessary to water for 19 hours to be used 7-day interval. Hydraulic design also determined that the pipe diameter is 63 mm. The pressure drop was set at 1.27 meters head. (Meters water column), and the minimum operating pressure is 24.35 PSI. Performance evaluation of the irrigation system in which it was found that the coefficient of uniformity (CU) 74.15% is still an acceptable value, as values Christianse subsequently made.